Improving the Quality of Citizenship Education Learning Through Citizenship Learning Practices (Citizen Project) - Roslinda, Roslinda (International Journal of Students Education, 2024)
In improving the moral quality and character of the nation’s children, it is necessary to implement early childhood citizenship education. Citizenship education has begun to be implemented since elementary school. Teachers have an important role in teaching and directing students to implement the values of citizenship education in everyday life. Therefore, teachers must have a strategy to increase students’ interest and motivation in citizenship education learning. In carrying out the teaching and learning process in this subject, teachers use learning models that are considered effective for improving the Quality of Citizenship Education Learning. One of them is by conducting citizenship learning practices (project citizen). Project citizen equips students to obtain a pleasant learning atmosphere, provides experience, and increases student knowledge. Project citizen learning functions to provide learning motivation to students through "fun learning" and activities carried out by students both inside and outside the classroom (Adha, 2010; Adha, 2018). This study aims to determine how to implement citizenship learning practices (project citizen) and increase student motivation in citizenship education learning. The method used in this study is a literature review study. The results of the study show that learning using the Project Citizen model can improve students’ critical thinking skills in finding and solving problems that occur.